Growth of African Catfish (Clarias gariepinus) in Illizi South-East Algeria - Ibrahim Elkhalil Behmene; Benabdallah Bachir Bouiadjra; Mohamed Daoudi; Abdelkader Homrani (Department of Aquaculture, 2021)
These observations are intended to provide information on the growth of the African catfish (Clarias gariepinus) living in the Oued Takhamalte-Illizi South-East Algerian. The basic data are the frequencies of the fish sizes resulting from the experimental fisheries carried out in October 2019 in Oued Takhamalte South-East of Algeria. The ELEFAN I program incorporated into FiSAT II software was used. The Powell-Wetherall method provides an L∞ of the order of 53.84 cm and a Z/K of 3.254 with a correlation coefficient R = - 0.944. This asymptotic length is greater than the maximum observed value (Lmax = 50 cm) and the Taylor approximation (L max/0.95 = 52.63 cm). The corresponding K value (0.28/year) seems the most suitable for the growth of a species, for this we opted for the parameters obtained by the sub-program « area of equal responses» of the program ELEFAN I (L∞ = 53 cm and K = 0.28/year) for the continuation of our study. The reduced gap test proves that there is a significant difference between the observed slope (b = 2.41) and the theoretical slope (P = 3), which makes it possible to affirm that the height-weight relationship in both sexes of C. gariepinus shows minor allometry, meaning that the weight grows slower than the cube of length.